Helping our students to be successful in their studies (a proposal based on teaching practice reflexions) - Sedano Gelvet, Eduardo (2001)
We propose eleven recommendations to help our students to be successful in their studies, and analyse their interactions and results implications in the outcome of the andragogic task. The purpose of this article is to suggest the practice of each recommendation in the university teaching, in the daily andragogic practice, in order to allow our students to discover knowledge happiness and love.